Dead again in Tombstone - Reine, Roel; Wiley, Ethan; Dysinger, Elaine; Trejo, Danny, 1944-; Busey, Jake; Rotaru, Elysia; McDermott, Dean, 1966-; Lavender, Elizabeth; Skagen, Peter; Rios, Michelle; Shaw, Joe Norman; Universal 1440 Entertainment (Firm); et al. (Universal City, CA : Universal Pictures Home Entertainment, 2017)
The devil's outlaw and reluctant servant, Guerrero returns from the dead again. Guerrero is forced to protect a stolen relic from getting into the hands of Jackson Boomer and his gang of soldiers, but Jackson will stop at nothing to raise his comrades from the dead and bring the wrath of hell upon earth. Guerrero must use all his dark powers in order to defeat Jackson and find redemption, or die again trying.
Wide screen (1.78:1)
Bonus features: Making Dead again in Tombstone ; Danny Trejo as Guerrero ; deleted shots montage ; feature commentary with director Roel Reine, editor Radu Ion, director of photography, Rolf Dekens, writer Ethan Wiley and Grid VFX CEO Jan Goossen.
Music, Hybrid; editor, Radu Ion; director of photography, Rolf Dekens.
Danny Trejo, Jake Busey, Elysia Rotaru, Dean McDermott, Elizabeth Lavender, Peter Skagen, Michelle Rios, Joe-Norman Shaw.
MPAA rating: R; for strong violence, sexuality, nudity and some language.
DVD; region 1; widescreen (1.78:1) presentation; Dolby digital 5.1 surround.
Keywords: Outlaws -- Drama; Gunfights -- Drama; Relics -- Drama; French language materials; Spanish language materials; Film sequels; Fiction films; Western films; Feature films; Video recordings for the hearing impaired; Drama